Pengembangan Media Pembelajaran Scrapbook untuk Meningkatkan Pemahaman Materi Struktur Bumi dan Dinamikanya - Rizal, Ahmad; Akhlis, Isa; Sarwi, Sarwi (UPEJ Unnes Physics Education Journal, 2019)
The purpose of this study is developing student worksheet use flipbook maker based on creative problem solving to increase critical thinking skill of senior high school student. Subject of this research is eleven Science four of senior high school Kesatrian 2 Semarang on school year 2017/2018. The method of this study is Development Research. The step of this research is preliminary step and formative evaluation step (self evaluation (analysis and design), prototyping, and field test). Prototyping step of student worksheet tested its characteristics and validity by material expert and media expert. Field test use Pre-test and Post-test One Group Design. Analysis data method used angket data analysis, validity analysis, normality analysis, t-test and gain test. The result assessment of student worksheet validity by material expert is 86, 44% with valid criteria and assessment by media expert is 83,12% with valid criteria. The result of implementation from student worksheet use flipbook maker based on creative problem solving to critical thinking skill increased after t-test showed Sig. (2-tailed) result is 0,000 and gain testing with score 0,37 with medium criteria. The result of this research showed that student worksheet use flipbook maker based on creative problem solving is valid and can be used to increase critical thinking skill of senior high school student.